2012
DOI: 10.2147/ijn.s30706
|View full text |Cite
|
Sign up to set email alerts
|

Coseeded Schwann cells myelinate neurites from differentiated neural stem cells in neurotrophin-3-loaded PLGA carriers

Abstract: Biomaterials and neurotrophic factors represent promising guidance for neural repair. In this study, we combined poly-(lactic acid-co-glycolic acid) (PLGA) conduits and neurotrophin-3 (NT-3) to generate NT-3-loaded PLGA carriers in vitro. Bioactive NT-3 was released stably and constantly from PLGA conduits for up to 4 weeks. Neural stem cells (NSCs) and Schwann cells (SCs) were coseeded into an NT-releasing scaffold system and cultured for 14 days. Immunoreactivity against Map2 showed that most of the grafted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…This was confirmed by the intense expression of APC, an oligodendrocyte marker, notably in the N-SCs + NSCs and NSCs + T-NSCs groups. The results are consistent with the known evidence that NT-3 promotes oligodendrocyte precursor cell (OPC) maturation and myelination [14,24]. We speculate that NT-3 may facilitate oligodendrocyte development through p75…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was confirmed by the intense expression of APC, an oligodendrocyte marker, notably in the N-SCs + NSCs and NSCs + T-NSCs groups. The results are consistent with the known evidence that NT-3 promotes oligodendrocyte precursor cell (OPC) maturation and myelination [14,24]. We speculate that NT-3 may facilitate oligodendrocyte development through p75…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is necessary to search for strategies to harness the therapeutic potential of NSCs in bridging lesion gap of SCI. One ideal counterstrategy would be to genetically strengthen the capacities of viability and lineage differentiation of NSCs into neurons and oligodendrocytes [13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Xiong et al [2012] showed that myelination occurred from Schwann cells in their PLGA matrix, which released NT-3 from silk fibroin. They utilized a high molecular weight PLGA with a 3: 1 ( D , L -lactide:glycolide) block copolymer, but more importantly utilized sodium chloride as a porogen to achieve a porous structure.…”
Section: Material-mediated Induction Of Maturation and Myelin Productionmentioning
confidence: 98%
“…However, in these studies myelination still occurred by Schwann cells rather than oligodendrocytes [Pittier et al, 2005]. Since then, numerous groups have observed myelination from Schwann cells in biomaterials [Gingras et al, 2008;Xiong et al, 2012;Thomas et al, 2014].…”
Section: Material-mediated Induction Of Maturation and Myelin Productionmentioning
confidence: 99%